Association between Uric Acid and Bone Mineral Density in Postmenopausal Women with Type 2 Diabetes Mellitus in China: A Cross-Sectional Inpatient Study - Xin Zhao; Xiaofeng Yu; Xiaomei Zhang (Journal of Diabetes Research)
Objective. To analyze the association between uric acid levels and bone mineral density in postmenopausal women with type 2 diabetes mellitus. Methods. We retrospectively analyzed 262 postmenopausal women with type 2 diabetes mellitus, to assess uric acid levels and bone mineral density using the T score of dual-energy X-ray absorptiometry. Results. (1) Women in the osteoporosis group demonstrated higher uric acid levels and lower estimated glomerular filtration rate (p<0.05, respectively). (2) Uric acid levels were positively correlated with the hip and lumbar spine bone mineral density and T score (r=0.17, p<0.05; r=0.25, p<0.05; r=0.17, p<0.05; and r=0.28, p<0.05, respectively). Meanwhile, there was a positive relation between estimated glomerular filtration rate and hip bone mineral density (r=0.22, p<0.05). (3) Logistic regression analysis showed that age, body mass index, and diabetic duration are independent risk factors for osteoporosis in postmenopausal women with type 2 diabetes mellitus. The level of estimated glomerular filtration rate and uric acid levels were not independent effect factors for osteoporosis in menopausal women. Conclusion. Uric acid levels are neither a protective factor nor a risk factor for osteoporosis in women with type 2 diabetes mellitus.